EVALUASI PROGRAM MICRO TEACHING PADA MAHASISWA PGMI UNIVERSITAS SULTAN MUHAMMAD SYAFIUDDIN SAMBAS MENGGUNAKAN MODEL KIRKPATRICK - Ahmad Rathomi; Sitti Mania; Muhammad Nur Akbar Rasyid (Berajah Journal, 2026)
This study aimed to evaluate the effectiveness of the micro teaching program implemented in the Primary Islamic Teacher Education (PGMI) Study Program using the Kirkpatrick evaluation model at the Reaction and Learning levels. The research employed a quantitative evaluation approach involving 21 students who had completed the micro teaching course. Data were collected through a Likert-scale questionnaire to measure students’ reactions and an observation rubric to assess teaching competencies. The data were analyzed using descriptive statistics, including mean scores, percentages, and effectiveness categories. Unlike previous studies that primarily examined the influence of micro teaching on teaching competence, this study evaluates the effectiveness of the program systematically by integrating participants’ reactions and learning outcomes within the Kirkpatrick evaluation framework in the context of Islamic teacher education. The findings revealed that the micro teaching program achieved an effectiveness score of 78.98% at the Reaction level, indicating that students generally responded positively to the program, particularly regarding the quality of supervising lecturers and the relevance of the program to professional development. At the Learning level, the program achieved an effectiveness score of 83.51%, categorized as highly effective, demonstrating significant improvement in students’ teaching competencies. The highest achievements were found in reinforcement skills, instructional variation, classroom management, and lesson opening and closing skills. Overall, the findings indicate that the micro teaching program effectively supports the development of pedagogical competencies and prepares PGMI students to perform professional teaching practices.